Therapeutic Strategies for Neuropathic Pain: Potential Application of Pharmacosynthetics and Optogenetics - Gum Hwa Lee; Sang Seong Kim (Hindawi Limited, 2016)
Chronic pain originating from neuronal damage remains an incurable symptom debilitating patients. Proposed molecular modalities in neuropathic pain include ion channel expressions, immune reactions, and inflammatory substrate diffusions. Recent advances in RNA sequence analysis have discovered specific ion channel expressions in nociceptors such as transient receptor potential (TRP) channels, voltage-gated potassium, and sodium channels. G protein-coupled receptors (GPCRs) also play an important role in triggering surrounding immune cells. The multiple protein expressions complicate therapeutic development for neuropathic pain. Recent progress in optogenetics and pharmacogenetics may herald the development of novel therapeutics for the incurable pain. Designer Receptors Exclusively Activated by Designer Drugs (DREADDs) facilitate the artificial manipulation of intracellular signaling through excitatory or inhibitory G protein subunits activated by biologically inert synthetic ligands. Expression of excitatory channelrhodopsins and inhibitory halorhodopsins on injured neurons or surrounding cells can attenuate neuropathic pain precisely controlled by light stimulation. To achieve the discrete treatment of injured neurons, we can exploit the transcriptome database obtained by RNA sequence analysis in specific neuropathies. This can recommend the suitable promoter information to target the injury sites circumventing intact neurons. Therefore, novel strategies benefiting from pharmacogenetics, optogenetics, and RNA sequencing might be promising for neuropathic pain treatment in future.